The Spockian Mother: Images of the "Good" Mother in Dr. Spock's The Common Sense Book of Baby and Child Care, 1946–1992. Issue 1 (1st January 2017) - Dobris, Catherine A.; White-Mills, Kim; Davidson, Rachel D.; Wellbrook, Toula V.
Abstract : Dr. Spock's, The Common Sense Book of Baby and Child Care, one of the best-selling self-help texts of all-time, "second only to the Bible in popularity" (Meakin & Tattersall, 2004) was one of the most influential childcare books in American culture. The author has been both heralded and disparaged as instrumental in the shaping of untold generations. In the present study, we address the rhetorical construction of the Spockian Mother as she is developed during Spock's tenure from 1946–1992. We employ a feminist rhetorical perspective to examine the progression of Spock's texts in order to understand how patriarchal images of motherhood are constructed and maintained through Spock's lifetime and the first 46 years of its publication. We argue that Spock both reinforced and challenged the institution of motherhood; he challenged institutionalized motherhood by encouraging mothers to "trust themselves" while simultaneously conforming to a patriarchal model of motherhood which is at odds with empowered mothering.